Implementasi Kebijakan Pakta Integritas dalam Peningkatan Kinerja Aparatur Publik (Studi pada Keputusan Bupati Madiun Nomor: 237 Tahun 2005 tentang Pakta Integritas di Lingkungan Pemerintah Kabupaten Madiun) - Nurlita Pravitasari (Jurnal Administrasi Publik, 2016)
Abstract : The implementation of the policy  Integrity Pact  In Performance Improvement of Public Apparatus (Studies in Madiun Regency Decree No : 237 of 2005 regarding Integrity Pact in Environmental Madison County). The integrity pact is used as a reference for Madiun district government in dealing with acts of corruption of public officials that happen in Madison County in accordance with the decision of the Regent Madiun number : 237 of 2005 on the integrity pact. The purpose of this study to determine the implementation of integrity pacts in improving the performance of the apparatus of public, based on the Decision Regent Madiun No. 237 of 2005 on Integrity Pact Governments Madison County, particularly the Kecamatan Wungu and the Kecamatan Balerejo and describe the inhibiting factors and the factors driving the implementation of integrity pacts in improving the performance of public officials. The results showed that the improved performance of the apparatus of public in Madison County, especially in Sub Balerejo and Kecamatan Wungu implemented effectively and accountable in accordance with the Decree of the Regent Madiun number : 237 in 2005, but has not been fully maximized because not all officials have the responsibility of the importance of integrity pact resulting in less than the maximum in providing services to the public which ultimately the vision and mission of the integrity pact can not be reached. Keywords: Policy Implementation, The Integrity Pact, Public Apparatus, Madison County Abstrak : Implementasi Kebijakan Pakta Integritas dalam Peningkatan Kinerja Aparatur Publik (Studi pada Keputusan Bupati Madiun Nomor: 237 Tahun 2005 tentang Pakta Integritas di Lingkungan Pemerintah Kabupaten Madiun). Pakta integritas digunakan sebagai acuan Pemerintah Kabupaten Madiun dalam menangani tindak penyelewengan aparatur publik yang terjadi di lingkungan Kabupaten Madiun sesuai dengan keputusan Bupati Madiun nomor : 237 tahun 2005 tentang pakta integritas . Tujuan dilakukannya penelitian ini untuk mengetahui implementasi pakta integritas dalam peningkatan kinerja aparatur publik, berdasarkan Keputusan Bupati Madiun Nomor: 237 Tahun 2005 tentang Pakta Integritas di Lingkungan Pemerintah  Kabupaten Madiun, khususnya Kecamatan Wungu dan Kecamatan Balerejo serta mendeskripsikan faktor penghambat dan faktor pendorong pelaksanaan pakta integritas dalam peningkatan kinerja aparatur publik. Hasil penelitian menunjukkan bahwa peningkatan kinerja aparatur publik di Kabupaten Madiun khususnya di Kecamatan Balerejo dan Kecamatan Wungu  dilaksanakan secara efektif dan akuntabel sesuai dengan Keputusan Bupati Madiun nomor : 237 tahun 2005, namun belum sepenuhnya maksimal karena tidak semua aparatur mempunyai tanggung jawab akan pentingnya pakta integritas yang mengakibatkan kurang maksimal dalam memberikan pelayanan kepada masyarakat yang akhirnya visi misi dari pakta integritas tidak dapat tercapai. Kata kunci: Implementasi Kebijakan, Pakta Integritas, Aparatur Publik, Kabupaten Madiun.